Black boxes and gray spaces: how illegal dwellings find regulatory loopholes - Lau, Questor (ARCC Conference Repository, 2014)
In Honolulu, the building permit process has been likened to a black box, synonymous with regulatory barriers and unbearable delays. In response, homeowners cultivate gray spaces: ambiguous accessory spaces such as "Hobby,” "TV” or "Rumpus Rooms” that are issued permits and then frequently converted illegally into an independent dwelling unit. In essence, these Illegal Accessory Dwellings function as non-permitted second units on land zoned for single-family use. This paper proposes to quantify the number of Illegal Accessory Dwellings in Honolulu, based on the number of residential buildings permits issued for spaces that could be easily converted into a separate rental unit. Using building permit data provides a systematic method to analyze all legally sanctioned building activity, pinpointing only those residential layouts that are highly suspicious for being converted into a separate rental unit. In so doing, this paper makes a key distinction: a structure can be built to code, but its occupancy – how it is used – can still be illegal. From 2005-2012, this paper found that Illegal Accessory Dwellings comprised a low of 30% upto 46% of all new one and two-family dwellings units created. The highest rate of production was in 2008, during the Great Recession. Thus, this paper suggests that Illegal Accessory Dwellings contribute a substantial number of units to the overall housing supply. This paper also raises questions such as – How are these units being counted in the official US Census? Are they counted as separate households or as part of the primary residence? Given the significant number of this type of housing, how Illegal Accessory Dwellings are characterized could potentially shift the landscape of where urban growth is occurring. Research methods include correlational research, GIS mapping and case studies, to explain how homeowners circumvent the rules.